Increasing agricultural production in Nepal: role of low-cost irrigation development through farmer participation - Pradhan, P. (International Irrigation Management Institute, 1989)
This book reveals that Nepal irrigation policy directives and resources must be channeled to encourage the participation of beneficiaries and to focus the functions of the Department of Irrigation on a management perspective . The low cost approaches recommended in the paper include : 1) incorporating farmer participation in operation and management, 2) considering lower cost structures in surface irrigation and underground water development and, 3) improving the management of irrigation systems